Colapso progressivo de edificações de concreto armado em construção - Sessa, Thiago da Cruz (2017)
Already in the 1970s it was found that the progressive collapse of existing buildings was rare, and that there was significant growth in cases of buildings under construction suffering horizontal and/or vertical collapse from an initial damage, causing many times loss of lives. History has shown that most failures of concrete structures occurred when they were still under construction. This brings to light the need for research and recommendations that aim to minimize the risk of the progressive collapse of not only existing structures but also those still under construction. This work summarizes structures design recommendations to prevent progressive collapse and lists cases of reinforced concrete buildings that had partial or total collapse while under construction or, when completed, still not in service. From these cases, it is possible to identify the most common causes of the occurred collapses and point out procedures to prevent them.